CHALLENGES AND OPPORTUNITIES OF IMPLEMENTING HALAL CERTIFICATION IN NONMUSLIM MAJORITY MARKETS - Siti Mujanah (Journal of Halal Research, Policy, and Industry, 2024)
This study examines the challenges and opportunities associated with implementing halal certification in non-Muslim majority markets. The research focuses on understanding the impact of the halal concept, certification costs, consumer perceptions, and consumer trust on sales growth in these markets. Using a quantitative approach, data was collected from 300 sellers operating in non-Muslim markets in Indonesia through an online survey distributed via Google Forms. The findings reveal a significant positive effect of the halal concept on increasing consumer trust.. Additionally, consumer perceptions were found to influence consumer trust significantly. Furthermore, increased consumer trust was positively associated with sales growth in non-Muslim markets. The study provides valuable insights for sellers aiming to navigate the challenges and leverage the opportunities of halal certification in non-Muslim majority markets. Strategies to enhance consumer trust and mitigate certification costs are suggested, along with avenues for future research to explore innovative solutions for improving the implementation of halal certification